Younger adult brain utilizes interhemispheric strategy via ipsilateral dorsal premotor cortex for fine control of dexterous finger movements, unlike the aging brain - Miura, Gen; Morita, Tomoyo; Park, Jihoon; Naito, Eiichi (Frontiers in Aging Neuroscience, 2025)
IntroductionThis study investigated how healthy, right-handed younger adults utilize the typically suppressed ipsilateral sensorimotor cortices [particularly, the dorsal premotor cortex (PMd), primary motor cortex (M1), primary somatosensory cortex (S1), and superior parietal cortex of Area 2] to perform a dexterous finger motor task and its age-related changes.MethodsFunctional magnetic resonance imaging was used to measure brain activity in healthy, right-handed younger and older adults during a simple button-press task with the right index finger and a dexterous stick-rotation task involving fine control and coordination of individual right finger movements. The individual performance capacity in stick rotation (the personal trait of finger dexterity) was assessed outside the scanner. The sensorimotor cortices (PMd, M1, S1, and Area 2) in each hemisphere were defined as regions-of-interest (ROIs), and contrast analysis, interparticipant correlation analysis with performance capacity, and interhemispheric functional connectivity analysis were performed.ResultsIn the younger group, all ipsilateral sensorimotor cortices were deactivated during the button-press task, whereas during the stick-rotation task, the PMd, S1, and Area 2 were activated, and the ipsilateral M1 remained deactivated. The ipsilateral PMd, S1, and Area 2 activity was correlated with performance capacity. During the stick-rotation task, the anterior ipsilateral PMd consistently enhanced interhemispheric functional coupling with all contralateral sensorimotor cortices. In contrast, in the older group, ipsilateral sensorimotor deactivation was not observed during the button-press task, and all ipsilateral cortices were activated during the stick-rotation task; however, none of the activity was correlated with performance capacity. In addition, functional connectivity within the contralateral sensorimotor cortices (rather than interhemispheric connectivity) increased during the stick-rotation task.ConclusionOur findings indicate that ipsilateral sensorimotor activity during the current dexterous task reflects different physiological mechanisms between younger and older adults. When performing the task, younger adults recruited the ipsilateral PMd, S1, and Area 2 by disinhibiting their interhemispheric inhibition to complement for their clumsiness; the ipsilateral PMd appeared important for the interhemispheric interaction, whereas the ipsilateral sensorimotor activity in older adults did not appear to represent proactive interhemispheric interaction to overcome clumsiness.